Study on the correlation between abnormal bone metabolism and cognitive impairment in type 2 diabetes mellitus - Li, Jiang; An, Yuxiao; Qin, Jian; Mohamad, Noor Shafini; Ramli, Izzad (Frontiers in Medicine, 2025)
IntroductionType 2 diabetes mellitus (T2DM) is often accompanied by bone metabolic disorders and cognitive impairment, forming an interactive network through metabolic derangements, oxidative stress, and inflammatory responses. Hyperglycemia and insulin resistance disrupt bone remodeling leading to osteoporosis while simultaneously impairing cognition via blood-brain barrier damage and neuroinflammation. Osteogenic factors like osteocalcin may bidirectionally regulate glucose metabolism and brain function, suggesting that “bone-brain axis” dysregulation could be a potential mechanism underlying cognitive impairment in T2DM. This study aims to characterize cognitive function patterns in T2DM patients with bone metabolic abnormalities and their clinical correlations, providing a basis for multisystemic interventions.MethodsThe general clinical data, osteocalcin (OC), glycosylated hemoglobin (HbA1c), bone mineral density (BMD), and the Montreal Cognitive Assessment (MoCA) scores of 50 patients with T2DM were collected. According to whether cognitive impairment occurred or not, one-way ANOVA was performed to analyze the correlation between cognitive and clinical indicators, BMD and OC. Multiple linear regression analysis was performed with cognition and bone density as dependent variables and other factors as independent variables.ResultsT2DM subjects were grouped according to bone mass. The osteoporosis group had the lowest MoCA score and bone density, followed by the osteopenia group. There were 16 cases (16/17 94.12%) of cognitive impairment in the osteoporosis group, 13 cases (13/17 76.47%) of cognitive impairment in the osteopenia group, and 3 cases (3/16 18.75%) of cognitive impairment in the normal bone mass group. Compared with the normal cognitive group, the MoCA score, OC measurement and BMD of the patients in the cognitive impairment group were lower (P < 0.05). BMD (r = 0.686, P = 0.000), OC (r = 0.756, P = 0.000) are positively correlated with MoCA score. OC (r = 0.690, P = 0.000) and Age (r = −0.032, P = 0.045) are positively correlated with BMD. Multivariate linear regression analysis found that with cognition as the dependent variable, the decrease in BMD (P = 0.028) and OC (P = 0.000) aggravated the occurrence of cognitive impairment; with BMD as the dependent variable, the decline in cognition (P = 0.028) and OC (P = 0.029) aggravated the decrease in BMD.ConclusionT2DM, osteoporosis, and cognitive impairment form pathological connections through metabolic disorders, chronic inflammation, and bidirectional regulatory networks of the “bone-brain axis,” with osteocalcin serving as a key mediator that maintains bone remodeling balance while also exerting cross-domain regulation over central insulin signaling and synaptic plasticity. Understanding these interactive mechanisms provides a basis for developing combined screening models integrating bone density and cognitive assessments, and promotes multidisciplinary collaborative interventions across endocrinology, orthopedics, and neurology to improve overall outcomes for T2DM patients.